Digitally-assisted power converter system for solar energy harvesting applications - Bui, Anh Khoa (2019)
Nowadays, the power management unit (PMU) plays an essential role in electronic and communication devices and their reliability. More challenges for the power management industries are proposed from the increasing of low-voltage low-power electronic devices and growing demands of complex functionalities. Limited capacity of the finite power source is one of the limitations on the overall performance and the lifetime of these battery-powered devices. “Energy harvesting” is the process of collecting and converting minute amount of unharnessed energy from surrounding environment into usable electrical energy. There are plenty of ambient energy sources ranging from the most common sources such as thermal energy, solar energy, and mechanical vibrations to new-developed sources like RF microwave, bioenergy, etc. As energy harvesting increases the possibility of autonomous devices, efficient energy harvesting circuit design has become increasingly important and has gained immense popularity. Scavenging energy from solar is a good solution to address the increase of power consumption in electronic devices. Modern circuits and systems require multiple voltage supplies to provide different functionalities. For example, 2.2-3V supplies power RF and antenna circuit, while analog circuit and digital circuit operate using different voltage supplies ranging from 0.6V to 1.8V. Using multiple voltage supplies can improve the overall performance while reducing the power consumption of the devices. viii In this research, an energy scavenging system is proposed to extract photovoltaic (PV) energy and supply to application smart nodes of Internet-of-Things (IOT). The main part of the system consists of a single-inductor H-bridge configuration DC-DC converter connecting with dual inputs and dual outputs. It aims to regulate a constant 1V output voltage to supply for several applications such as signal transmitters and sensor. The surplus energy is stored in a super capacitor. The backup capacitor also serves as a secondary source of energy. The most critical issue in energy harvesting applications is maximum power extracting. In order to maximize power extraction under all conditions, a digital-controlled feed-forward maximum power point tracking (MPPT) system is implemented. An input approximation method is proposed to quickly predict the change in input power and shift the PV system to operate the maximum power point (MPP). Both pulse-frequency modulation (PFM) and pulse-width modulation (PWM) are then used to regulate the 1V output voltage at the MPP. The PV system is designed using 0.18μm CMOS technologies. The controller part is mostly designed using digital circuit to enhance stability, reliability, and controllability. The system is able to extract energy from a single solar cell and deliver to multiple outputs loads. The proposed system achieves above 60% of conversion efficiency with a peak efficiency of 84.1% while driving 1μA to 1mW load current. The next part of this research evaluates the possibility of using switched-capacitor (S) DC-DC converter in battery-powered electronic devices. Different designs of SC converter are proposed. The first design presents a single boundary ix hysteretic controller for a SC converter. It can achieve optimal output voltage ripple by matching the converter switching frequency and the output sampling frequency. This ½ step-down SC converter is fabricated in 0.18μm CMOS technologies, using on-chip flying capacitors. The proposed design can achieve peak conversion efficiency of 86% while maintains power conversion efficiency higher than 65% while deliver output loads from 0.1mA to 7mA. In addition, a SC converter with integrated NMOS-LDOs is proposed to further improve the transient response and eliminate the output ripple. The power switches of the SC converter are functioned as the pass transistor of the low-dropout regulators. Adaptive gate slop technique and gate pre-charge technique are used to reduce output glitches as well as optimize the dead time during phase transitions. The second SC converter is also implemented in 0.18μm CMOS technologies. It achieves peak efficiency of 83% while maintains the efficiency higher than 72% throughout the entire load range.